Construction of the Performance Marketing Model of Superior Product in the One Village One Product (OVOP) Program - Sijabat, Rauly; Fataron, Zuhdan Adi (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: The decline in the number of MSME players and marketing performance is an indication of the effectiveness of the OVOP program towards the down streaming of marketing performance of SMEs in leading products assisted by Islamic banking in Central Java. These findings led this study to find empirically variables that could explain the problem of marketing performance by using a competitive advantage variable approach, business networking capabilities, HR competencies, financial factors, and operational factors. Design/methodology/approach: The influence of marketing performance, competitive advantage, business networking capabilities, HR competencies, financial factors, and operational factors are visualized in the empirical model tested in this study using the Structural Equation Modeling (SEM) analysis technique approach. Findings: The results of the tests conducted show that competitive advantage is built through the capabilities of business networks, HR competencies, financial factors and operational factors where financial factors are the main explanation. The test results also show that competitive advantage is proven to be a variable that can explain the occurrence of variations in marketing performance. Research limitations: The predictors examined in this study are still limited to internal factors and do not involve other factors outside MSMEs. Practical implications: Increasing business networking capabilities, HR competencies, financial factors and operational factors. Originality/value: This research develops an empirical model to explain marketing performance in leading MSMEs Paper type: Research paper